Synthesis and characterization of transition metal with hydrazone/carbohydrazone ligand - Farhanna, bte. Hj Umar @ Omar. (Universiti Malaysia Sarawak, (UNIMAS), 2008)
Five transition metal complexes ofcarbohydrazone-bis(benzaldehyde) ligand (1) with transition metal ions [M = Mn(ll), Co(II), Ni(ll), Cu(ll) and Zn(II)] have been synthesized and refluxing with methanol in I: I mole ratio (metal:ligand). Another two metal complexes ofbenzophenone-salicylhydrazone ligand (2) with transition metal ions [M = Cu(II) and Ni(II)] have also been synthesized in the presense of base and refluxing in methanol in I:2: I mole ratio (metal:base:ligand). All metal complexes (3-9) have been characterized using CRN analyses, UV-Visible and FTIR spectral studies. Among them, ligand (2) and its nickel(II) complex (9) have also been characterized by lH NMR. All transition metal complexes (3-9) are non electrolyte in nature. Spectral studies suggested that ligand (1) act as a mononegative tridentate nature toward central metal ion while the ligand (2) act as 8 mononegative bidentate nature in their metal complexes.